Audit Sistem Informasi Menggunakan Cobit 5.0 Domain DSS pada PT Erajaya Swasembada, Tbk - Wella Wella (Universitas Multimedia Nusantara, 2016)
The object of research is PT Erajaya Swasembada, Tbk. The company was founded in 1990, running a business as a distributor of mobile phones, which has outlets in various cities in Indonesia. Studied business processes includes sales, purchasing, finance, and warehouse, ERP (Enterprise Resource Planning). The research was conducting an audit of information technology governance at PT Erajaya Swasembada, Tbk, which is more focused on users who are involved in the cycle of the company’s Enterprise Resource Planning use. Auditing information technology governance using the COBIT 5.0 framework, focusing on the domain Deliver, Service, and Support (DSS). The results obtained from this study is any process that exist in the domain Deliver, Service, and Support (DSS) is in level 3 (established process) and 4 (predictable process) capability models. For DSS01, DSS02 and DSS06 is at level 4, while for the DSS03, DSS04 and DSS05 is at level 3. The company has already implemented the service and support of information technology governance is well proven from their operational procedures in the provision of services to internal and external, incident handling procedures, and maintenance control of appropriate business processes. Service and support of information technology remains to be improved in a sustainable manner. Key Words: Audit; IT Governance Audit; COBIT 5.0; Deliver; Service; and Support (DSS); Capability Model.